Qualitative research approaches for studying local food environment and drivers of food purchase in South Asia - Custodio, Marie Claire; Samaddar, Arindam; Ynion, Jhoanne; Banerjee, Deep; Mohanty, Suva; Patel, Jigar; Veettil, Prakashan Chellattan (2022)
The High Level Panel of Experts on Food Security and Nutrition (2017)’s definition of the food environment has been expanded to include the significant issue of sustainability and the different types of food environment relevant to low- to middle-income countries (Downs et al., 2020), while Turner et al. (2018) builds on food environment research into the socio- ecological theory that posits that inter- related personal and environmental factors determine health-related behaviors.